FIGURATIVE LANGUAGE IN SELECTED SONGS OF ARIANA GRANDE'S ALBUM : ETERNAL SUNSHINE - Tiodame Layupa; Nabilah Siti Haniyah, Dimas Abdul Ramadhan, Deniela Yoshelyn (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This research examines the use of figurative language in selected songs from Ariana Grande's “Eternal Sunshine” album. The primary objective is to analyze the figurative expressions through a detailed lyrical analysis. The analysis categorizes the figurative language into four main types: simile, metaphor, personification, and hyperbole. The findings indicate that metaphors are the most prevalent, with 18 occurrences, followed by hyperboles with 9 occurrences, personifications with 4 occurrences, and similes with 3 occurrences, totaling 34 instances of figurative language. These literary devices enhance the emotional and thematic depth of the music, fostering a deeper connection between the listeners and the material. This study contributes to understanding the role of figurative language in contemporary music and highlights the artistic intricacies in Ariana Grande compositions. Employing a descriptive qualitative methodology, the research focuses on five specific tracks from the album, underscoring the significance of figurative language in songwriting.